1994
DOI: 10.1016/0732-8893(94)90026-4
|View full text |Cite
|
Sign up to set email alerts
|

A five-year multicenter study of the susceptibility of the Bacteroides fragilis group isolates to cephalosporins, cephamins, penicillins, clindamycin, and metronidazole in the United States

Abstract: Over 2800 clinical strains of the Bacteroides fragilis group were collected during a 5-year period from ten geographically separate sites and tested for their susceptibility to various antimicrobial agents using a broth microdilution method. Among the cephalosporins, ceftizoxime was the most active (13% resistance) and importantly exhibited relatively equal activity against both B. fragilis species and non-B. fragilis species. Cefotaxime exhibited similar activity with an overall resistance rate of 18%. Both c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
16
0

Year Published

1995
1995
2009
2009

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 24 publications
2
16
0
Order By: Relevance
“…fragilis species. However, the latter group exhibited more resistance (3,6,23) indicate the continued in vitro activity of metronidazole against the B. fragilis group species. However, Rotimi et al (20) reported clinical failures due to metronidazole-resistant isolates of the B. fragilis group and detected high-level cross-resistance to imipenem, meropenem, piperacillin, piperacillin-tazobactam, clindamycin, and cefoxitin.…”
Section: Resultsmentioning
confidence: 99%
“…fragilis species. However, the latter group exhibited more resistance (3,6,23) indicate the continued in vitro activity of metronidazole against the B. fragilis group species. However, Rotimi et al (20) reported clinical failures due to metronidazole-resistant isolates of the B. fragilis group and detected high-level cross-resistance to imipenem, meropenem, piperacillin, piperacillin-tazobactam, clindamycin, and cefoxitin.…”
Section: Resultsmentioning
confidence: 99%
“…The Anaerobe Working Group for the National Committee for Clinical Laboratory Standards (NCCLS) recommends that susceptibility testing of the B. fragilis group be done with a distribution of test isolates to approximate the species distribution normally isolated from infections (7). Several multicenter susceptibility studies have shown that the B. fragilis species comprises 58 to 63% of isolates (1,5,6,17). Such distribution rates have been relatively evident in studies reported during the 1980s and early 1990s.…”
mentioning
confidence: 93%
“…The B. fragilis species unexplainably remains more susceptible to many antimicrobial agents than the other species within the group (1,7,17). It is therefore important, especially in the choice of empirical therapy, that sufficient susceptibility data from sufficient numbers of isolates be available for local or regional isolates.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Published articles reveal only a few reported cases of B. fragilis that were resistant to metronidazole (6-10). Although the incidence of resistance to penicillin, cephalosporins, and clindamycin is increasing dramatically, no resistance to metronidazole in B. fragilis was found in some large-scale studies done throughout the world (11,12).…”
mentioning
confidence: 99%